Psychotropic Medication Experiences of Incarcerated Women: A Qualitative Inquiry into Conundrums of Access and Identity. Issue 1 (2nd January 2019) - Casey, Rachel C.; Bentley, Kia J.
Abstract : The study examines narrative data from in-depth, semi-structured interviews with 25 women in a medium security prison with the hope of deepening the knowledge base related to women's beliefs about their mental health problems, mental health care during incarceration, and especially their experiences with psychotropic medication. The findings highlight the functional role of psychotropic medication in the lives of incarcerated women, while also emphasizing problems with limited access to prescribers, preferred medications, and other forms of mental health treatment. Trauma, substance use, and the impact of medication use on sense of self all emerged as interfacing with quality of life.